GROWTH RESPONSE OF 3YEARS AGE JERNANG RATTAN PLANT (Daemonorops draco Willd.) ON LIGHT INTENSITY UNDER MIXED STAND AT KHDTK KEMAMPO, BANYUASIN REGENCY - Nopriansyah, Andi; Aluyah, Cik; Sosilawati, Endang (Universitas Muhammadiyah Palembang, 2021)
Rattan jernang (Daemonorops draco Willd.) is a type of non-timber forest product that has a high market value. To reduce dependence on natural forests, jernang rattan cultivation is important. This study aims to determine the growth response of 3 year old jernang rattan plants to light intensity under mixed stands. The study was carried out at KHDTK Kemampo, Palembang Environmental and Forestry Research and Development Center from June to July 2020. This study used an experimental method with a Non-Factoral Randomized Block Design consisting of 3 treatments with 9 replications. The treatments consisted of P1 = canopy closure 10–30% (light intensity 72.19%), P2 = canopy closure 40–60% (light intensity 55.63%), and P3 = canopy closure 70–90% (light intensity 23.39%). The results showed that the growth of jernang rattan gave a very good response to light intensity under mixed stands for all parameters observed, namely plant height, leaf midrib length and number of leaves, as well as leaf color. The best growth of jernang rattan is in light conditions with a canopy cover of 10%-30% (light intensity 72.19%). There is a positive correlation between light intensity and the growth of jernang rattan under mixed stands, that is, the higher the light intensity, the better the growth of jernang rattan.